Technology, motivation, and English writing competence in EFL classroom among Indonesian undergraduate students - Ivo Dinasta Yanuar (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2023)
The rapid development of digital technology offers a new environment for English teaching and learning. It potentially improves the English learners' motivation and achievement in English writing skills. This paper investigated how technology usage related to the student's English learning motivation and writing skills in the Indonesian context. This study applied a quantitative method and used the test and online questionnaire as instruments. A pre-test and a post-test were used to find the significant improvement of English writing skills. Meanwhile, the a-ten online questionnaires were distributed to the students to investigate their motivation in English writing. The result shows that technology contributes to the development of the students' competence in the class of English writing as well as students' motivation in English writing learning. Significant correlations were also found between the pre-test and the post-test for undergraduate students. The implication of this study arises for English language pedagogy, especially in the Indonesian university context. The English language teaching especially focusing on writing is not only strengthened from the linguistics outcomes, but also non-linguistics outcomes such as motivation. Then, the pedagogy and technology integration must be considered to achieve English learning goals.Keywords:Â motivation, English language learning, technology, English writing achievement